ADVANTAGES AND DISADVANTAGES ARTIFICIAL INTELLIGENCE-BASED AUDIOVISUAL HISTORIOGRAPHY: Kelebihan dan Kekurangan Historiografi Audio-Visual Berbasis Kecerdasan Buatan - Daya Negri Wijaya; Evania Yafie; Primasa Minerva Nagari; Firza Azzam Fadilla; Muhammad 'Afwan Mufti (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This article explores the transformative potential of artificial intelligence (AI) in reshaping audiovisual historiography, a field that integrates historical inquiry with multimedia representation. This article employs a qualitative-descriptive approach to understand the strengths and limitations of applying artificial intelligence (AI) technology in audiovisual historiography. The primary data sources for this study are a comprehensive literature review of relevant scholarly articles and books, as well as data from the creation of short historical videos using the AI platform Invideo.Io. This article investigates how AI-based tools enable the curation, restoration, and reinterpretation of historical narratives. It also highlights key advancements in AI applications, including the automatic transcription of archival audiovisual material, deepfake-based reconstructions, and immersive virtual reconstructions of historical events. This article further examines the opportunities and challenges posed by these innovations. The findings indicate that AI technology can offer unprecedented accuracy, accessibility, and creative possibilities in historical storytelling. On the other hand, concerns regarding ethical misuse, historical distortion, and digital authenticity require a robust framework to ensure credibility and accountability. For example, the AI-generated historical videos from Invideo.Io have shortcomings related to accuracy and synchronization between visuals and factual narratives of historical events. The findings of this study illustrate that AI can democratize history and make it more accessible, provided that a robust ethical framework is in place. This article contributes to our understanding of how emerging technologies can shape the future of historical research and storytelling.